Editorial: Revisit the roles of regulatory T cells in infection - Zhou, Xuyu; Zhao, Jingxian; Li, Bin; Tai, Xuguang (Frontiers in Immunology, 2022)
Although Tregs are essential for preventing autoimmunity, their functionality in modulating the immune response against foreign antigens remains poorly defined. A series of recent contributions in Frontiers in Immunology have discussed the potential role of Treg response for foreign antigens in various settings, including infections and vaccination.